2016
DOI: 10.1002/cre2.26
|View full text |Cite
|
Sign up to set email alerts
|

Basic characteristics of plasma rich in growth factors (PRGF): blood cell components and biological effects

Abstract: Platelet‐rich plasma (PRP) is widely used in regenerative medicine because of its high concentrations of various growth factors and platelets. However, the distribution of blood cell components has not been investigated in either PRP or other PRP derivatives. In this study, we focused on plasma rich in growth factors (PRGF), a PRP derivative, and analyzed the distributions of platelets and white blood cells (WBCs). Peripheral blood samples were collected from healthy volunteers (N = 14) and centrifuged to prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Both erythrocytes and leukocytes were almost completely eliminated in the process of preparation and the platelets were significantly concentrated by 2.84 fold. 30 The antimicrobial activity of PRGF has been demonst rated by its effect against the four staphylococci strains, reaching its maximum during the first few hours after application. 31 Few studies which showed anti-microbial effect of pure platelet-rich plasma (P-PRP) against Enterococcus faecalis, Candida albicans, Streptococcus agalactiae, Streptococcus oralis and Pseudomonas aeruginosa, showed that P-PRP inhibited the growth of all 3 strains but not of Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Both erythrocytes and leukocytes were almost completely eliminated in the process of preparation and the platelets were significantly concentrated by 2.84 fold. 30 The antimicrobial activity of PRGF has been demonst rated by its effect against the four staphylococci strains, reaching its maximum during the first few hours after application. 31 Few studies which showed anti-microbial effect of pure platelet-rich plasma (P-PRP) against Enterococcus faecalis, Candida albicans, Streptococcus agalactiae, Streptococcus oralis and Pseudomonas aeruginosa, showed that P-PRP inhibited the growth of all 3 strains but not of Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin gel is a biological material that can be used in the autologous system and is a high-density fibrin network that includes a large number of biologically active compounds, the main of which are PDGF (platelet-derived growth factor), TGF (transforming growth factor), FGF (fibroblast growth factor) and IGF (insulin-like growth factor) [31]. These growth factors can affect the metabolic processes of cells and play a major role in regulating the process of reparation and regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, plasma rich in growth factors (PRGF) of autologous origin have previously been demonstrated to introduce several advantages, including the enhancement and acceleration of bone regeneration and, additionally, fast and predictable soft tissue healing [18][19][20][21]. Once the platelets become activated, the growth factors and cytokines within the alpha and dense granules are released.…”
Section: Introductionmentioning
confidence: 99%